Antioxidant capacity, polyphenol content and iron bioavailability from algae (Ulva sp., Sargassum sp. and Porphyra sp.) in human subjects - García-Casal, Maria N.; Ramírez, José; Leets, Irene; Pereira, Ana C.; Quiroga, Maria F. (British journal of nutrition, 2009)
Marine algae are easily produced and are good sources of Fe. If this Fe is bioavailable, algae consumption could help to combat Fe deficiency and anaemia worldwide. The objective of the present study was to evaluate Fe bioavailability, polyphenol content and antioxidant capacity from three species of marine algae distributed worldwide. A total of eighty-three subjects received maize- or wheat-based meals containing marine algae (Ulva sp., Sargassum sp. and Porphyra sp.) in different proportions (2·5, 5·0 and 7·5 g) added to the water to prepare the dough. All meals administered contained radioactive Fe. Absorption was evaluated calculating radioactive Fe incorporation in subjects' blood. The three species of marine algae were analysed for polyphenol content and reducing power. Algae significantly increased Fe absorption in maize- or wheat-based meals, especially Sargassum sp., due to its high Fe content. Increases in absorption were dose-dependent and higher in wheat- than in maize-based meals. Total polyphenol content was 10·84, 18·43 and 80·39 gallic acid equivalents/g for Ulva sp., Porphyra sp. and Sargassum sp., respectively. The antioxidant capacity was also significantly higher in Sargassum sp. compared with the other two species analysed. Ulva sp., Sargassum sp. and Porphyra sp. are good sources of bioavailable Fe. Sargassum sp. resulted in the highest Fe intake due to its high Fe content, and a bread containing 7·5 g Sargassum sp. covers daily Fe needs. The high polyphenol content found in Sargassum sp. could be partly responsible for the antioxidant power reported here, and apparently did not affect Fe absorption.